User-Friendly Evaluation of Three-Dimensional Visualization of Atomic Models on Mobile Teaching Module Application: PyLo-AR - Ramadhan, Imam; Hasyim, Mutahharah; Nurlina, Nurlina (Department of Physics, Faculty of Mathematics and Natural Sciences, 2024)
Integrating augmented reality technology in physics education provides students with a novel learning experience, requiring proficient skills and effective organization. PyLo-AR, a Marker-Based Augmented Reality (M-AR) mobile app, teaches atomic models (Dalton, Thomson, Rutherford, Bohr). This study assesses PyLo-AR's user-friendliness using SUS and UEQ methods, involving highschool students. SUS scores indicate a satisfactory usability level (71). UEQ averages are 1.797 (Attractiveness), 1.700 (Perspicuity), 1.577 (Efficiency), 1.605 (Dependability), 1.941 (Stimulation), and 1.067 (Novelty). The category of the stimulation indicator is excellent, which means the PyLo-AR application is highly engaging for learners. The attractiveness, efficiency, and accuracy indicators are rated as